2009
DOI: 10.1093/molbev/msp037
|View full text |Cite
|
Sign up to set email alerts
|

Layers of Evolvability in a Bacteriophage Life History Trait

Abstract: Functional redundancy in genomes arises from genes with overlapping functions, allowing phenotypes to persist after gene knockouts. Evolutionary redundancy or evolvability of a genome is one step removed, in that functional redundancy is absent but the genome has the potential to evolve to restore a lost phenotype. Exploring the extent to which this recovery alters gene networks can illuminate how functional gene interactions change through time. Here, the evolvability of lysis was studied in bacteriophage T7,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 46 publications
4
21
0
Order By: Relevance
“…Accordingly, it is suggested that some unknown factors other than holin, lysozyme, and spanins are involved in the lysis pathway of T7 phage. Heineman et al (14) also suggested that T7 contains additional holins, as their optimality failed to predict the lysis time of T7 phage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, it is suggested that some unknown factors other than holin, lysozyme, and spanins are involved in the lysis pathway of T7 phage. Heineman et al (14) also suggested that T7 contains additional holins, as their optimality failed to predict the lysis time of T7 phage.…”
Section: Discussionmentioning
confidence: 99%
“…Phage burst size was measured as previously described (14), with some modifications. Briefly, a BL21 culture at an A 595 of 0.3 to 0.4 was infected with phages at a multiplicity of infection (MOI) of 0.02.…”
Section: Methodsmentioning
confidence: 99%
“…Deletion of the chaperone-like protein gp1 in both deletion mutants Ms6 ⌬gp4 and Ms6 ⌬gp5 was catastrophic for lysis, with more than 3-fold reduction of the burst size, even though the mutant phage are viable and could be isolated. Remarkably, although Gp5 was unable to allow endolysin-mediated lysis in E. coli, a mutant phage lacking both gp1 and gp4 was able to infect M. smegmatis cells and undergo lysis, so it is expected that there will be alternative pathways to release phage progeny (13). We conclude that for mycobacteriophage Ms6 and related mycobacteriophages, the presence of the endolysin in addition to one of the lytic genes, gp1, gp4, or gp5, is sufficient for a lysis phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Although essential for the establishment of lysogeny, the fact that no mutations occurred in these genes suggests that they do not participate in adaptive evolution of the decision making process. These observations follow an emerging theme in experimental studies of microbes: evolution often finds solutions other than those that are nominated a priori, despite an often very detailed knowledge of the system in question (e.g., Blount et al 2008;Beaumont et al 2009;Harris et al 2009;Heineman et al 2009;McDonald et al 2009).…”
Section: Discussionmentioning
confidence: 73%